2020
DOI: 10.1080/02640414.2020.1860296
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematics Comparison of Different Swimming Relay Start Techniques

Abstract: In swimming relay races, various start techniques are performed by swimmers, but it remains unclear which technique leads to a better start performance. Therefore, the purpose of the present study was to compare the kinematic characteristics of different relay start techniques with the new starting block Omega OSB11. Eleven international youth swimmers were filmed during 1) no step with parallel feet, 2) no step with separated feet and 3) one-step starts and their centre of mass kinematics calculated with 2D-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, from then on, 13 out of 19 research studies employed at least 100 Hz, with 100-120 Hz being the most common selection. This is in line with frame rates reported in research about swimming starts [50] or turns [51].…”
Section: Study Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…However, from then on, 13 out of 19 research studies employed at least 100 Hz, with 100-120 Hz being the most common selection. This is in line with frame rates reported in research about swimming starts [50] or turns [51].…”
Section: Study Characteristicssupporting
confidence: 91%
“…Filtering procedures for the continuous raw data of UUS typically consisted of a low-pass Butterworth filter with cut-off frequencies that ranged from 4 to 7 Hz, with 6 Hz being the most common frequency. These cut-off frequencies are usually employed in swimming motion [52], although they are lower than those employed for the swimming starts [50]. The calculation of real space coordinates from the screen (digitised) coordinates was performed by either mean of linear scaling techniques or DLT algorithms [30] in 16 out of 25 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the experimental condition, distances traveled underwater from a dive start (lap 1) were 3-3.5 m longer than when pushing off the turning wall (laps 2 and 3). This represents a greater difference than the typical flight distances observed in elite youth swimmers during dive starts (Qiu et al, 2021), but differences were confirmed by the greater number of underwater kicks observed in lap 1 vs. laps 2 and 3 (Figure 3).…”
Section: Discussionmentioning
confidence: 72%
“…In order to adapt to the interaction between multiple endpoints and the migration of future cloud services, a network structure of an underwater swimming posture intelligent detection model was adopted [13][14]. This model constructs a unified support service layer that can achieve unified support services for desktop, mobile, and future web pages.…”
Section: Video Surveillance Based On Computer Visionmentioning
confidence: 99%